British propaganda to France, 1940-1944 : machinery, method and message / Tim Brooks. - Brooks, Tim (Timothy William) (International communications., 2007)
This book examines the important issue of British propaganda to France during the Second World War and aims to show the value of the propaganda campaign to the British war effort. British Propaganda to France is a unique contribution to the field, not only in its examination of one of the least well-studied areas of British activity during the Second World War but also in the breadth of its approach. It surveys the organisation, operation and nature of the British propaganda effort towards the French people, including both white propaganda (BBC broadcasts and leaflets dropped by the RAF) and black propaganda (secret broadcasting stations, documents purporting to come from the Germans in France or distributed in France using clandestine methods, and rumours). Finally it examines the contemporary British understanding of the French and German reception of and reaction to this propaganda material, to show whether the campaign was an effective and well-directed use of resources. Almost all examinations of British foreign propaganda during the Second World War have focused on propaganda directed towards Germany. British propaganda to France, which in terms of quantity of output was actually the most important area of British propaganda, has never been examined in depth until now. This book adds a further chapter to our knowledge of propaganda in the Second World War, especially in the conduct of psychological warfare. It also touches on better-known areas such as RAF Bomber Command and its Operational Training Units, which handled aerial dissemination of British white propaganda leaflets over France, and the Special Operations Executive in France, which worked closely with the Political Warfare Executive in delivering much black propaganda."